AH-41 Morphology of Mandibularis and Lingualis Glands of Laughting Chicken (Ayam Gaga) with Special Refferences of Distribution and Content of Carbohydrate - Muhammad Syukur Hamdan; Novi Susanty; I Ketut Mudite Adnyane; Dwi Kesuma Sari (Media Veteriner, 2015)
Morphology of Mandibularis and Lingualis Glands of Laughting Chicken (Ayam Gaga) with Special Refferences of Distribution and Content of Carbohydrate